Clinical outcomes following implantation of the ION™ paclitaxel‐eluting platinum chromium coronary stent in routine clinical practice: Results of the ION U.S. post‐approval study. Issue 3 (30th December 2018) - Cannon, Louis A.; Kimmelstiel, Carey D.; White, Anthony; Hill, Roger; Grady, Timothy P.; Myers, Paul R.; Underwood, Paul; Dawkins, Keith D.
Abstract: Background: The ION Study assessed clinical outcomes for the thin‐strut, ION™ (TAXUS Element) Paclitaxel‐Eluting Platinum Chromium Coronary Stent System (Boston Scientific, Marlborough, MA) in unselected patients. Methods: This prospective, open‐label registry enrolled the first 1, 120 consenting patients treated with the ION stent without clinical or angiographic inclusion criteria at 40 clinical sites. Follow‐up was at discharge, 30 days, 180 days, 1 and 2 years. The primary endpoint, the 1‐year rate of cardiac death or MI (CD/MI) in PERSEUS‐like patients (i.e., patients similar to those enrolled in PERSEUS, the pivotal approval trial), was tested in patients pooled from the ION study (N = 316), the European TAXUS Element post‐approval registry (TE‐PROVE; N = 306 PERSEUS‐like patients), and the PERSEUS WH/SV populations (N = 1, 166); and then compared with a prespecified performance goal. Additional outcomes were examined in the overall ION patient population. Results: A total of 1, 111 (out of 1, 120) enrolled patients received a study stent. Most patients were male (70%) and mean age was 64 years. At 1 year, the primary endpoint of CD/MI occurred in 2.1% (6/292) of PERSEUS‐like patients in ION, and 2.3% (40/1, 729) of patients in the combined analysis. The upper one‐sided 95% confidence interval for the combined analysis was 2.9%, which was significantly less than the performance goal of 7.6% ( P < 0.001). Within patients enrolled in the ION study (N = 1, 111), the rate of CD/MI was 4.5% at 1 year and 7.5% at 2 years. Definite/probable stent thrombosis occurred in 2.1% of patients at 1 year and 2.5% at 2 years. Conclusions: The results of the ION Study confirm the mid‐term safety and effectiveness of the ION stent for the treatment of coronary artery disease in everyday clinical practice.